P77 SIGNIFICANCE OF NEOADJUVANT DOWNSTAGING IN CARCINOMA OF THE ESOPHAGUS AND GASTRO-ESOPHAGEAL JUNCTION. (23rd November 2019) - Kamarajah, S K; Navidi, M; Wahed, S; Immanuel, A; Hayes, N; Griffin, S M; Phillips, A W
Abstract: Aim: The aim of this study was to determine the importance of cTNM and ypTNM, and impact of downstaging of disease in patients with esophageal or gastro-eesophageal junction (GOJ) carcinoma who received neoadjuvant treatment followed by surgery. Background: Most locally advanced esophageal cancers are treated with neoadjuvant therapy (chemotherapy or chemoradiotherapy). TNM staging is used prior (cTNM) and after (ypTNM) neoadjuvant treatment and surgery. Methods: Data from consecutive patients with esophageal cancer from a single center were evaluated. Patients with either adenocarcinoma or squamous cell carcinoma of the esophagus who were treated with neoadjuvant chemo(radio) therapy followed by transthoracic esophagectomy and two-field lymphadenectomy were included. Comparison of outcomes with those primarily treated with surgery was made. The cTNM and ypTNM were applied and compared according to the American Joint Commission on Cancer (AJCC) 8 th edition staging system. Results: This study included 1115 patients of which 486 patients received surgery alone and 629 patients received neoadjuvant therapy and resection. Of patients receiving neoadjuvant therapy, 9 (1%) had cTNM stage 2 and 451 (72%) had a cTNM stage 3. Rates of downstaging were similar in esophageal adenocarcinoma and SCC (54% vs 62%, p=0.4). Downstaging was associated with significantly longer survival than patients with no change for both adenocarcinoma (median: 48 vs 15 months, p<0.001) and SCC (median: NR vs 17 months, p<0.001). On adjusted Cox regression, downstaging was associated with significantly longer survival in patients for esophageal adenocarcinoma but not SCC. Conclusion: This study demonstrates ypTNM stage is provides a better estimate of prognosis compared to clinical stage. Downstaged patients may have an improved outcome over those with comparable pathological stage that did not receive neoadjuvant treatment.